Специфіка виборчих кампаній у Північній Америці: порівняльні аспекти - Іваненко, Альона Євгеніївна (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi
Keywords: Міжнародні відносини, виборча кампанія, Північна Америка